Switch [compact disc, unabridged] : how to change things when change is hard - Heath, Chip (Random House Audio, 2010)
Offers insight into the difficult nature of lasting change, presenting metaphorical illustrations of the conflict between the instinctual and the intellectual areas of the brain while sharing case stories of successful individuals and organizations.